Ohio under COVID: Lessons from America's Heartland in Crisis (University of Michigan Press, 2023)
In early March of 2020, Americans watched with uncertain terror as the novel coronavirus pandemic unfolded. One week later, Ohio announced its first confirmed cases. Just one year later, the state had over a million cases and 18,000 Ohioans had died. What happened in that first pandemic year is not only a story of a public health disaster, but also a story of social disparities and moral dilemmas, of lives and livelihoods turned upside down, and of institutions and safety nets stretched to their limits. Ohio under COVID tells the human story of COVID in Ohio, America’s bellwether state. Scholars and practitioners examine the pandemic response from multiple angles, and contributors from numerous walks of life offer moving first-person reflections. Two themes emerge again and again: how the pandemic revealed a deep tension between individual autonomy and the collective good, and how it exacerbated social inequalities in a state divided along social, economic, and political lines. Chapters address topics such as mask mandates, ableism, prisons, food insecurity, access to reproductive health care, and the need for more Black doctors. The book concludes with an interview with Dr. Amy Acton, the state’s top public health official at the time COVID hit Ohio. Ohio under COVID captures the devastating impact of the pandemic, both in the public discord it has unearthed and in the unfair burdens it has placed on the groups least equipped to bear them.